Determinants of maternal healthcare services utilization in selected communities in Edo Central Senatorial District Nigeria - Elusoji, Christiana I.; Ugochukwu, Chika G.; Eze, Clementina N.; Udo, Mary A.; Nwafor, Amauchechukwu V.; Azuogu, Victoria C.; Onyeabor, Juliana O.; Ohanme, Eugene Ohams (International Journal of Research in Medical Sciences, 2023)
Background: Throughout history, society has always employed several means to promote maternal healthcare services to save pregnant women and their unborn babies from expected or unexpected dangers during pregnancy, birth and after birth. This study investigated the determinants of maternal health care services utilization in selected communities. Methods: A descriptive cross-sectional survey design was adopted for this study using a questionnaire as a quantitative tool. The population of the study comprised women of reproductive age group (15-49) Edo Central Senatorial District, Edo State Nigeria. A multi-stage sampling technique was used to select 561 study participants from the target population. A total of 561 copies of the questionnaire were administered but 490 of them were retrieved and found to meet criteria for analysis. Data was analyzed using SPSS version 25 and computed for descriptive statistics- frequency with percentage counts, mean and standard deviations. Additionally, inferential statistics chi-square used to test the stated hypotheses. Results: The finding showed that the women’s mean age of 28±5.37. Residential location of the participants did not significantly influence their utilization of maternal healthcare services. Educational qualifications, were found to influence the utilization of maternal healthcare services than those of lower educational levels (p<0.05). In addition, 364 (74.2%) respondents agree that free or low cost of maternal health services would prompt and promote regular visits to clinic. Conclusions: It is recommended that the government should provide freer or low-cost.